An explanatory investigation on the role of communication antecedents in project management - Karuppiah S.D.; Marthandan G.; Shanmugam M. (Little Lion Scientific, 2023)
Project management has become a norm in many organizations for project benefit realization commonly aligned to organizational strategic goals. These projects in organizations create additional value to meet organization commitments. Research suggests that communication management is one of the key area in project management. This research therefore embarks empirically to determine the role of project communication impacting project management. The identified antecedents of communication are adapted from Media Synchronicity Theory (MST) to study the impact on communication performance influencing project management. The study uses data gathered by a survey involving respondents from the IT industry analyzed using the Partial Least Squares of the Structural Equation Modeling (PLS-SEM). The empirical evidence demonstrates a significant relationship between communication and project management. The study also contributes to the project management body of knowledge. 2005 ongoing JATIT & LLS.